The Collaborative Ocular Tuberculosis Study (COTS)-1 Report 3: Polymerase Chain Reaction in the Diagnosis and Management of Tubercular Uveitis: Global Trends. (3rd April 2019) - Agarwal, Aniruddha; Agrawal, Rupesh; Gunasekaran, Dinesh Visva; Raje, Dhananjay; Gupta, Bhaskar; Aggarwal, Kanika; Murthy, Somasheila L.; Westcott, Mark; Chee, Soon Phaik; McCluskey, Peter; Ling, Ho Su; Teoh, Stephen; et al.
ABSTRACT: Purpose : To analyze the role of polymerase chain reaction (PCR) of ocular fluids in management of tubercular (TB) anterior, intermediate, posterior, and panuveitis. Methods : In Collaborative Ocular Tuberculosis Study (COTS)-1 (25 centers, n = 962), patients with TB-related uveitis were included. 59 patients undergoing PCR of intraocular fluids (18 females; 53 Asian Indians) were included. Results : 59 (6.13%) of COTS-1 underwent PCR analysis. PCR was positive for Mycobacterium TB in 33 patients (23 males; all Asian Indians). 26 patients were PCR negative (18 males). Eight patients with negative PCR had systemic TB. Anti-TB therapy was given in 18 negative and 31 PCR cases. At 1-year follow-up, five patients with positive PCR (15.15%) and three with negative PCR (11.54%) had persistence/worsening of inflammation. Conclusions : Data from COTS-1 suggest that PCR is not commonly done for diagnosing intraocular TB and positive/negative results may not influence management or treatment outcomes in the real world scenario.